Peran Bidan dalam Parenting Education Sebagai Upaya Peningkatan Tumbuh Kembang Anak Usia Dini - Tri Sunarsih Tri Sunarsih (AIPKIND (Asosiasi Pendidikan Kebidanan Indonesia), 2015)
Implementation of health promotion through parenting education in holistic integrative earcly childhood education (PAUD) is a medium for parental education to improve parenting to children, so that children can grow and develop optimally. Holistic integrative education in early childhood among Posyandu, Education for Family with Toddler, and Early Childhood Education is a new paradigm; thus, there is a need for a strategy that combines three aspects: nutrition, health, psychosocial, and education. This research aimed to analyze the influence of the role of village midwife in health promotion process through parenting education in holistic integrative PAUD that impacts directly or indirectly on parenting parents holistically in Karanganyar District. This research was conducted in the Region of Karanganyar District, Central Java. This was a survey research with a cross-sectional design, using questionnaires as the main instrument to collect primary data. Secondary data were obtained from records in the relevant agencies in Karanganyar District. The sample size was 108 parents, taken by using purposive sampling technique. This research used multiple linear regression analysis and path analysis model. The findings were that, simultaneously and partially, the roles of village midwife, PAUD educator, and family planning outreach worker as well as the process of health promotion through parenting education had significant effects both directly and indirectly on holistic parenting. Strategy for health promotion through appropriate parenting education can be done with the improvement of multi sectoral cooperation.